Epistemología del saber matemático escolar: una experiencia didáctica. - Gabriela Buendía Ábalos; Javier Lezama Andalón (Nóesis)
In this paper we discuss the contribution of an epistemological reflection on the mathematical knowledge to school mathematics teacher through an experience in a master's degree in mathematics education. This discussion will be through the presentation of the course design and its development and showing some of the interactions with the participants through aspects such as the nature of the philosophical and epistemological discussion to understand the mathematical creation, the contribution that gives the historical review epistemology of knowledge, the recognition of the complexity of mathematics and mathematics education and the recognition of the teacher's own epistemology.